Glanzmann thrombasthenia secondary to a Gly273-->Asp mutation adjacent to the first calcium-binding domain of platelet glycoprotein IIb. - Poncz, M (1994)
We studied the defect responsible for Glanzmann thrombasthenia in a patient whose platelets expressed < 5% of the normal amount of GPIIb-IIIa. Genetic and biochemical evidence indicated that the patient's GPIIIa genes were normal. However, DNA analysis revealed the patient homozygous for a G818-->A substitution in her GPIIb genes, resulting in a Gly273-->Asp substitution adjacent to the first GPIIb calcium-binding domain. To determine how this mutation impaired GPIIb-IIIa expression, recombinant GPIIb containing the mutation was coexpressed with GPIIIa in COS-1 cells. The GPIIb mutant formed stable GPIIb-IIIa heterodimers that were not immunoprecipitated by either of two heterodimer-specific monoclonal antibodies, indicating that the mutation disrupted the epitopes for these antibodies. Moreover, the GPIIb in the heterodimers was not cleaved into heavy and light chains, indicating that the heterodimers were not transported from the endoplasmic reticulum to the Golgi complex where GPIIb cleavage occurs, nor were the mutant heterodimers expressed on the cell surface. These studies demonstrate that a Gly273-->Asp mutation in GPIIb does not prevent the assembly of GPIIb-IIIa heterodimers, but alters the conformation of these heterodimers sufficiently to impair their intracellular transport. The impaired GPIIb-IIIa transport is responsible for the thrombasthenia in this patient.